2020
DOI: 10.14571/brajets.v13.n3.319-328
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Education and the Undergraduate Dance Student’s Body Image: A Qualitative Study

Abstract: Regarding dance practitioners, body image associated with dance movement is a dynamic and complex phenomenon involving internal processes that cause impact on the psychological, emotional and behavioural areas. Balance between internal and external body experience is crucial for the construction of body image, and is associated with the way the student acquires knowledge about his own movement. In many contexts of dance teaching-learning, we found a focus centred almost exclusively on the reproduction of movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…= 41 Cont. = 43 EDI-3 BDD-YBOCS-SR SPIN BAAS IQ CES-D ABC To explore the experimental effects of involvement reduction in behaviors related to appearance in appearance concerns and related symptoms It provides robust evidence for the importance of safety behaviors related to appearance in the maintenance of body dysmorphic disorder and other body image-related disturbances 33 79% 8 Rato and Alves ( 2020 ) Portugal SM Somatic movement Women and man ( nW = 9; nM = 1) Classes It integrates the dance curriculum plan Psychoeducation 20 sessions (1 semester) No follow-up No control group Semi-structured interviews in depth; interviews of explanation; participants’ diaries and group discussions To study the body image of dance students, through the development and application of a Somatic Movement program in a group of undergraduate dance students The conscious utilization combined with multiple methods, such as in-depth semi-structured interviews; explanation interviews, group discussions, participants’ diaries, and field notes of the researcher brought significant advantages during the intervention 24 57% 9 Aboody et al ( 2020 ) Israel Mobile app for body image resilience Women ( nW = 91) Mobile app Training Cognitive-behavioral 14 days (4 min/day) (up to level 54) + a task of resilience on Instagram 1 month Randomization 1:1 BAS-2 VAS PASTAS DASS-21 BIDQ SISE To evaluate the effects of a cognitive-behavioral-based mobile app, projected to enhance the resilience to body image triggers and to reduce the symptoms of body image perturbances The results highlight the potential utility of brief portable interventions of low intensity in reducing symptoms of body image perturbances and enhancing resilience to messages of thin bodies often propagated on social media 28 67% 10 Glashouwer et al ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…= 41 Cont. = 43 EDI-3 BDD-YBOCS-SR SPIN BAAS IQ CES-D ABC To explore the experimental effects of involvement reduction in behaviors related to appearance in appearance concerns and related symptoms It provides robust evidence for the importance of safety behaviors related to appearance in the maintenance of body dysmorphic disorder and other body image-related disturbances 33 79% 8 Rato and Alves ( 2020 ) Portugal SM Somatic movement Women and man ( nW = 9; nM = 1) Classes It integrates the dance curriculum plan Psychoeducation 20 sessions (1 semester) No follow-up No control group Semi-structured interviews in depth; interviews of explanation; participants’ diaries and group discussions To study the body image of dance students, through the development and application of a Somatic Movement program in a group of undergraduate dance students The conscious utilization combined with multiple methods, such as in-depth semi-structured interviews; explanation interviews, group discussions, participants’ diaries, and field notes of the researcher brought significant advantages during the intervention 24 57% 9 Aboody et al ( 2020 ) Israel Mobile app for body image resilience Women ( nW = 91) Mobile app Training Cognitive-behavioral 14 days (4 min/day) (up to level 54) + a task of resilience on Instagram 1 month Randomization 1:1 BAS-2 VAS PASTAS DASS-21 BIDQ SISE To evaluate the effects of a cognitive-behavioral-based mobile app, projected to enhance the resilience to body image triggers and to reduce the symptoms of body image perturbances The results highlight the potential utility of brief portable interventions of low intensity in reducing symptoms of body image perturbances and enhancing resilience to messages of thin bodies often propagated on social media 28 67% 10 Glashouwer et al ( …”
Section: Resultsmentioning
confidence: 99%
“…Another example is the study by Rato and Alves ( 2020 ), which focused on a Somatic Movement program integrated into the dance bachelor’s curriculum, revealing that the conscious and combined use of multiple methods provided significant advantages during the intervention. Moore et al ( 2011 ) investigated a 12-week resistance training program, demonstrating significant improvements in self-perception constructs at all levels of the Exercise and Self-Esteem Model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it indicated that higher appearance-based exercise could weaken these aspects. Rato & Alves (2020) [30] reported that body image was associated with movement a complex phenomenon that impacted the dancers' psychology, emotion, and behavior These derived and indicated psychological characteristics of perfectionism are particularly high for concern over mistakes, personal standards, parental expectations, and doubts about actions to support and emphasize discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic education has received substantial academic attention in various dancing curricula, and efforts have been made to expand the definition of somatic education. Somatics has been defined by Rato and Alves (2019) as the science and art of interrelation processes among the environment, biological functioning and awareness, all of which are understood to be in synergy. The benefits of mindfulness, somatic exercises and Pilates include increased body awareness, and improved alignment, strength and a sense of sensory authority.…”
Section: Pilates Methods and Somatic Practicesmentioning
confidence: 99%